2013
DOI: 10.1093/bja/aet123
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain epidemiology and its clinical relevance

Abstract: Chronic pain affects ∼20% of the European population and is commoner in women, older people, and with relative deprivation. Its management in the community remains generally unsatisfactory, partly because of lack of evidence for effective interventions. Epidemiological study of chronic pain, through an understanding of its distribution and determinants, can inform the development, targeting, and evaluation of interventions in the general population. This paper reviews current knowledge of risk markers associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
340
0
32

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(384 citation statements)
references
References 68 publications
12
340
0
32
Order By: Relevance
“…It was possible that the acute event leading to hospitalization exacerbated one's baseline chronic pain, necessitating the use of opioids for pain control at discharge. [77][78][79][80][81] Prior research shows that chronic opioid therapy is associated with hospital readmissions. 82 In our patients, increased 'number of hospital readmissions' was correlated with 'opioid receipt' at discharge.…”
Section: Discussionmentioning
confidence: 99%
“…It was possible that the acute event leading to hospitalization exacerbated one's baseline chronic pain, necessitating the use of opioids for pain control at discharge. [77][78][79][80][81] Prior research shows that chronic opioid therapy is associated with hospital readmissions. 82 In our patients, increased 'number of hospital readmissions' was correlated with 'opioid receipt' at discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Although various medical and mental conditions, such as diabetes mellitus, hypertension, cardiovascular disease [32] and depression [9,11] are recognized as risk factors for SD, chronic pain is not typically regarded as one of them. The higher levels of pain reported by patients with SD as compared to those who did not report SD in the present study may suggest that chronic pain could also be considered a risk factor for SD, as suggested by others [9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Pain is a symptom of two of the three largest causes of death throughout the world, which in many cases cause extreme suffering which is frequently unrelieved (Van den Beuken-van Everdingen et al 2007, Goldberg and McGee 2011, van Hecke et al 2013. Nurses have a fundamental duty to both care for patients and relieve suffering, however this review of undergraduate pre-registration nursing education in the UK demonstrates that pain is an infrequent component of the curriculum.…”
Section: Discussionmentioning
confidence: 93%
“…Chronic pain effects around 20% of the adult population in Europe (van Hecke et al 2013) with chronic lower back pain alone identified as one of the top 10 diseases in the Global Burden of Disease Study (2010) and accounting the for highest number of Disability Adjusted Lost years (DALYS) globally (Murry et al 2012, World Health Organisation 2013. Incidence of acute pain prevalence across a range of conditions in inpatient settings also remains high (Ogboli-Nwasor et al 2012, Jabusch et al 2015, with estimates of 40-65% of inpatients reporting moderate to severe "worst pain.…”
Section: Accepted Manuscriptmentioning
confidence: 99%